FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KINERJA PERAWAT RAWAT INAP DI RSUD KOTA SEMARANG - Yohana Novitasari Sutrisno; Antono Suryoputro; Eka Yunila Fatmasari (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Nurses are the spearhead of hospitals in providing health service and should be managed professionally to improve the performance. The quality or satisfaction of nursing care was connected to nurses’ performance. Nursing care quality of the hospital was determined by patient satisfaction. Complaint data of inpatient patient at Regional Public Hospital of Semarang there were some complaints in nursing care. On the other side, the nurses were still complaining about the workload, leadership, promotion and supervision. The purpose of this study was to determine the related factors of nurses’ performance in inpatient unit at Regional Public Hospital of Semarang. The method of this research was using explanatory research with cross sectional approach. The population was all nurses in inpatient unit at Regional Public Hospital of Semarang with 71 peoples as sample. The analysis of the data was employed univariate and bivariate analysis with Rank Spearman Test. The result showed that variabels associated with the performance of nurses in inpatient unit at Regional Public Hospital of Semarang and has strong connection were workload (p value 0,001 and rs 0,554), leadership (p value 0,001 and rs 0,623), incentive (p value 0,001 and rs 0,680), and promotion opportunity has weak connection (p value 0,025 and rs 0,266). While the supervision is no associated with the performance of nurses in inpatient unit at Regional Public Hospital of Semarang (p value 0,794). Suggestion for the hospital are they have to rearrange the amount of the nurse, to evaluate incentive system, do some periodic coaching to all the nurses.